Inclusive Digital Technology and Islamic Education: Promoting Social Equity for Persons with Disabilities in the Digital Age - Afif, Faishal Nur Haidar; Musyaffa, Zaim Hilmi (Universitas Muhammadiyah Surakarta, 2025)
Persons with disabilities continue to face significant barriers in accessing digital technologies, particularly within educational contexts. The lack of inclusive design and limited digital literacy have contributed to a growing accessibility gap, reducing their ability to fully participate in social, economic, and religious life. This study aims to examine the role of inclusive digital technology in promoting social equity for persons with disabilities and its alignment with the values of Islamic education. A descriptive qualitative approach was employed using library research methods. Data were collected from a range of secondary sources, including international journals, national academic publications, NGO reports, and classical and contemporary Islamic literature. The findings reveal that technologies such as screen readers, voice recognition systems, and virtual assistants significantly enhance digital accessibility and independence for individuals with disabilities. The application of Universal Design for Learning (UDL) principles also proves effective in creating inclusive online educational environments. From an Islamic ethical perspective, digital inclusion is consistent with the objectives of maqāṣid al-sharī‘ah, particularly in preserving religion, intellect, and life. The study implies that collaborative efforts between Islamic educational institutions, technology developers, and policymakers are essential to embed the principles of justice and inclusivity in sustainable digital transformation